Effect of Ashwagandha (Withania Somnifera) Root Extract Against Gentamicin Induced Changes of Serum Urea and Creatinine Levels in Rats - Shimmi, Sadia Choudhury; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2012)
Background: Kidney is an important excretory organ. Its damage can be occurred due to prolonged use and higher doses of drugs, exposure to some chemicals, toxins, or infectious agents. Herbal plants as Ashwagandha (Withania somnifera) may have free radical scavenging activity thereby can be used for the prevention and treatment of kidney damage. Objective: To observe the nephroprotective effect of Ashwagandha (Withania somnifera) root against gentamicin induced nephrotoxicity in Wistar albino rats. Methods: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st July 2010 to 30th June 2011. A total number of 35 Wistar albino rats, age ranged from 90 to 120 days, weighing between 150 to 200 grams were included in this study. After acclimatization for 14 days, they were divided into control group (Group A) and experimental group (Group B). Control group was again subdivided into group A1 (baseline control, consisted of 10 rats) and group A2 (gentamicin treated control group, consisted of 10 rats). Again, experimental group (Group B- Ashwagandha pretreated and gentamicin treated group) consisted of 15 rats. All groups of animals received basal diet for 22 consecutive days. In addition to this, group A2 also received gentamicin subcutaneously (100mg /kg body weight/day) for the last eight (15th to 22nd day) consecutive days. Again, group B received ashwagandha root extract (500mg/kg body weight/ day; orally) for 22 consecutive days and gentamicin subcutaneously (100mg/kg body weight /day) for last eight (15th to 22nd day) days. All the animals were sacrificed on 23rd day. Then blood and kidney sample were collected. Estimation of serum urea, creatinine levels were done by using standard Laboratory kits. The statistical analysis was done by one way ANOVA and Bonferroni test as applicable. Results: The mean serum urea, creatinine levels were significantly (p<0.001) higher in gentamicin treated control group in comparison to those of baseline control. Again, these levels were significantly (p<0.01) lower in ashwagandha pretreated and gentamicin treated group (experimental group) when compared to those of gentamicin treated group (control). Conclusion: Ashwagandha (Withania somnifera) root may have some nephroprotective effect against gentamicin induced nephrotoxicity. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9756 JBSP 2011 6(2): 84-89